Usability Analysis of the DKI Jakarta Online Tax Application Using the System Usability Scale (SUS) Method - dimas faris noorfauzi; Muhammad Al-Makky; Kusuma Adi Ahmad (STMIK Banjarbaru, 2023)
The DKI Jakarta Online Tax Application is an application launched by the Jakarta City government to make it easier for the public in terms of renewing STNK, BPKB, and annual tax for both two-wheeled and four-wheeled vehicles, and much more. This application functions to speed up the long offline process by simply accessing the application and including the vehicle number to get a queue ticket or check prices. This research was conducted by collecting primary data through questionnaires to a total of 400 respondents who are DKI Jakarta residents who use the DKI Jakarta Online Tax application to determine the level of user satisfaction with the DKI Jakarta Online Tax application for the City of Jakarta using Usability Testing and System Usability Scale (SUS), the number of respondents this is sufficient based on the calculation of the number of samples from the existing population. The results of this study indicate that the DKI Jakarta Online Tax application gets a score of 50.31 with a